Effectiveness and cost-effectiveness of group support psychotherapy delivered by trained lay health workers for depression treatment among people with HIV in Uganda: a cluster-randomised trial. Issue 3 (March 2020) - Nakimuli-Mpungu, Etheldreda; Musisi, Seggane; Wamala, Kizito; Okello, James; Ndyanabangi, Sheila; Birungi, Josephine; Nanfuka, Mastula; Etukoit, Micheal; Mayora, Chrispus; Ssengooba, Freddie; Mojtabai, Ramin; Nachega, Jean B; et al.
Summary: Background: WHO recommends the use of psychological interventions as first-line treatment for depression in low-income and middle-income countries. However, evaluations of the effectiveness and cost-effectiveness of such interventions among people with HIV are scarce. Our aim was to establish the effectiveness of group support psychotherapy (GSP) delivered by lay health workers for depression treatment among people living with HIV in a rural area of Uganda on a large scale. Methods: In this cluster-randomised trial, we included 30 health centres offering HIV care. These were randomly assigned to deliver either GSP or group HIV education (GHE). Randomisation, in a ratio of 1:1, was achieved by health centre managers separately picking a paper containing the intervention allocation from a basket. Participants were people living with HIV, aged 19 years and older, with mild to moderate major depression assessed with the Mini International Neuropsychiatric Interview depression module, taking antiretroviral therapy, and antidepressant-naive. Group sessions were led by trained lay health workers once a week for 8 weeks. The primary outcomes were the proportion of participants with major depression and function scores at 6 months post-treatment, analysed by intention to treat by means of multilevel random effect regression analyses adjusting for clustering in health centres. This trial is registered with the Pan African Clinical Trials Registry, PACTR201608001738234. Findings: Between Sept 13 and Dec 15, 2016, we assessed 1473 individuals, of whom 1140 were recruited from health centres offering GSP (n=578 [51%]) or GHE (n=562 [49%]). Two (<1%) participants in the GSP group were diagnosed with major depression 6 months post-treatment compared with 160 (28%) in the GHE group (adjusted odds ratio=0·01, 95% CI 0·003–0·012, p<0·0001). The mean function scores 6 months post-treatment were 9·85 (SD 0·76) in the GSP group and 6·83 (2·85) in the GHE group (β=4·12; 95% CI 3·75–4·49, p<0·0001). 36 individuals had 63 serious adverse events, which included 25 suicide attempts and 22 hospital admissions for medical complications. The outcomes of these serious adverse events included 16 deaths, 4 of which were completed suicides (GSP=2; GHE=2), and 12 of which were HIV-related medical complications (GSP=8; GHE=4). Cost-effectiveness estimates showed an incremental cost-effectiveness ratio of US13·0 per disability-adjusted life-year averted, which can be considered very cost-effective in Uganda. Interpretation: Integration of cost-effective psychological treatments such as group support psychotherapy into existing HIV interventions might improve the mental health of people living with HIV. Funding: MQ Transforming Mental Health and Grand Challenges Canada.